INCREASING LEARNING MOTIVATION FOR VII.4 CLASS STUDENTS IN THE LEARNING PROCESS OF PPKN THROUGH THE APPLICATION OF THE TREFFINGER MODEL AT SMPN 17 PALEMBANG - Yusni Widawaty; Umi Chotimah (Sriwijaya University Learning and Education International Conference, 2018)
This study aims to increase the learning motivation of students in class VII. 4 in the PPKn learning process through the application of the Treffinger model in SMPN 17 Palembang. The research method used is Classroom Action Research (CAR), which is carried out in two cycles. Each cycle consists of four stages: planning, implementation, observation and reflection. Data was collected using observation and interview techniques. Furthermore, those who were the subject of the study were students of class VII.4 first semester in SMPN 17 Palembang, total 32 people consisting of 18 girls students and 14 boys students. The results showed that through the application of the Treffinger learning model can increase the learning motivation of students in class VII.4 of SMPN 17 Palembang. This is evident from the increased motivation of students from before the research until the end of the second cycle. Increased motivation in the first cycle of the first meeting reached 50% and the second meeting reached 62.5% of students which was marked by the learning activity of students, but not exceeding the success indicators of CAR, thus continuing with second cycle. In the second cycle, there was an increase in the third meeting reaching 72% and at the fourth meeting reached 81.25% of students who were active and creative in the question and answer presentation, because it has exceeded the indicators of success so it can be concluded that through the application of the Treffinger model increases participants' learning motivation VII.4 class students in the PPKn learning process at SMPN 17 Palembang.